Pengertian Pengembangan Kurikulum Pendidikan Agama Islam - Meylina Astuti; Jessika Mutiara; Mustafiyanti Mustafiyanti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
PAI curriculum development is the process of preparing, implementing, evaluating and perfecting the PAI curriculum. Curriculum is one of the important components that must exist in the world of education. Because without a curriculum, teachers will experience difficulties when carrying out their duties in the teaching and learning process. The curriculum in the learning process is a guide and guidance for educators. Every educator has an obligation to understand, master and develop the curriculum, because the curriculum is the most important system in the educational context, especially in Islamic religious education. By understanding and mastering the curriculum, teachers can choose and determine learning directions and objectives, learning methods, learning techniques, learning media, and learning evaluation tools that are appropriate to the material that will be used for teaching and learning. In achieving the goal of a good learning process, first facing and responding to the challenges of the dynamics of social change at this time, curriculum development is not only the task of the government and the highest office holders in Islamic education institutions, teachers are also expected to play their role in developing the Islamic religious curriculum in institutions Islamic education.